The Anxiety Level Of 3rd Trimester Primigravida Pregnant Woman In Facing Labor - Astutik, Puji; Erni Tri Indarti (Journal for Research in Public Health, 2025)
Pregnancy is a condition in which women experience different physiological changes and stress and is accompanied by unique physical and psychological demands. For primigravida pregnant women, pregnancy is the first experience in their life. This situation can result in drastic changes in both the mother's physical and physiology. In general, feelings of anxiety in pregnant women arise from things such as fear of giving birth, worry about changes in their body, the health of the fetus, and worry about caring for a child when the child is born. The aim of this research was to determine the level of anxiety of 3rd trimester primigravida pregnant women in facing childbirth in Blongko Village, Ngetos District, Nganjuk Regency. This research used a descriptive design which was carried out on July 12 2023 in Blongko Village, Ngetos District, Nganjuk Regency. The population in this study was 18 primigravida trimester 3 pregnant women, the sample size was 18 respondents, 3 trimester primigravida pregnant women with a sampling technique, namely total sampling, the variable in this study was the anxiety level of 3 trimester primigravida pregnant women in facing childbirth. The research instrument used the PRAQ-R2 (Pregnancy Related Anxiety Questionnaire Revised) questionnaire. Based on the research results from 18 respondents, almost all of them, namely 14 respondents (78%) had a severe level of anxiety, a small portion, namely 4 respondents (22%) had a moderate level of anxiety, and none, namely 0 respondents (0%) had an anxiety level. light category. The research results showed that almost all of them had a severe level of anxiety when facing childbirth. This is influenced by the education and employment of primigravida pregnant women in the third trimester. The higher a person's education level, the more qualified they will be in terms of knowledge. Mothers who have jobs will get information and experiences about pregnancy from other people, while mothers who spend most of their time at home will experience higher anxiety than working mothers. Therefore, health workers are recommended to provide health education to primigravida pregnant women in the third trimester in preparation for childbirth.